EXPLORING IELTS LISTENING: COMMON QUESTION FORMATS WITH EXAMPLES ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
: This article provides a comprehensive overview of the IELTS Listeningsection, outlining the different types of questions and offering practical examples and tipsfor each. It highlights the key question formats such as multiple-choice, matching, flow- chart completion, and short-answer questions, offering readers clear explanations andstrategies to tackle each one effectively. The article emphasizes the importance of practice, listening comprehension, and time management, encouraging readers to familiarizethemselves with different accents, content types, and paraphrasing techniques. Theconclusion underscores the significance of preparation for success in the IELTS Listeningtest, ultimately improving both test performance and real-world listening skills. Thisresource is useful for IELTS candidates aiming to improve their listening proficiency andachieve a high score in the exam.